Persepsi Harga dan Electronic Word of Mouth: Apakah Berpengaruh Terhadap Keputusan Pembelian Barang Elektronik di Tokopedia? - Devanty Kamila Maulidiya; Septiyani Dwi Anggreani; Yuni Zulfiana; Nidzam Zahra Viandifa; Khairani Zikrinawati; Zulfa Fahmy (Student Research Journal, 2023)
Electronic goods are secondary needs for the community (Investor Daily in the Ministry of Industry of the Republic of Indonesia, 2019) which are easily found in the online marketplace. However, purchasing electronic goods online requires higher accuracy, especially the variety of electronic goods that continue to grow makes it increasingly difficult for consumers to evaluate the product to be purchased. So to facilitate the evaluation process, consumers often make purchases based on price as a determinant of product quality (Tobing & Sihombing, 2016). The purpose of this study is to determine the influence of price perception and electronic word of mouth on electronic goods purchasing decisions on Tokopedia. The sampling technique used in this study is to use probability sampling techniques, namely simple random sampling. The sample in this study was 85 respondents and the data collected were analyzed using multiple linear regression through SPSS. The results of this study show that price perception and electronic word of mouth have a significant effect with a probability of significance of (0.013 < 0.05) on the purchase decision of electronic goods on Tokopedia.